2021
DOI: 10.3390/ma14205990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of A-Site Cation Deficiency on Charge Transport in La0.5−xSr0.5FeO3−δ

Abstract: The electrical conductivity of La0.5−xSr0.5FeO3−δ, investigated as a function of the nominal cation deficiency in the A-sublattice, x, varying from 0 to 0.02, has demonstrated a nonlinear dependence. An increase in the x value from 0 to 0.01 resulted in a considerable increase in electrical conductivity, which was shown to be attributed mainly to an increase in the mobility of the charge carriers. A combined analysis of the defect equilibrium and the charge transport in La0.5−xSr0.5FeO3−δ revealed the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…This possibly explains the lattice expansion with A-site non-stoichiometry. These results agree with the work by Merkulov et al They observed lattice expansion with A-site deficiency in La 0.5– x Sr 0.5 FeO 3−δ and ascribed it to the generation of oxygen vacancies in order to compensate for A-site vacancies to fulfill the electroneutrality requirements . In the literature, other studies have pointed out cation–oxygen bond rearrangement upon creation of A-site vacancies, which can cause bond length enlargement, thus expanding the lattice.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This possibly explains the lattice expansion with A-site non-stoichiometry. These results agree with the work by Merkulov et al They observed lattice expansion with A-site deficiency in La 0.5– x Sr 0.5 FeO 3−δ and ascribed it to the generation of oxygen vacancies in order to compensate for A-site vacancies to fulfill the electroneutrality requirements . In the literature, other studies have pointed out cation–oxygen bond rearrangement upon creation of A-site vacancies, which can cause bond length enlargement, thus expanding the lattice.…”
Section: Resultssupporting
confidence: 91%
“…These results agree with the work by Merkulov et al They observed lattice expansion with A-site deficiency in La 0.5−x Sr 0.5 FeO 3−δ and ascribed it to the generation of oxygen vacancies in order to compensate for A-site vacancies to fulfill the electroneutrality requirements. 40 In the literature, other studies have pointed out cation−oxygen bond rearrangement 41−43 upon creation of Asite vacancies, which can cause bond length enlargement, thus expanding the lattice. Thus, it seems that there is not a consensus on the mechanism that drives the lattice expansion upon the introduction of A-site vacancies.…”
Section: E V a L U A T I N G C O − F E − N I E X S O L U T I O N F R O Mmentioning
confidence: 99%
“…For the sake of comparison, a similar plot for the La 0.5 Sr 0.5 FeO 3− δ composition taken from ref. 32 is presented in this figure, which demonstrates a substantially wider interval of oxygen content variation.…”
Section: Resultsmentioning
confidence: 86%
“…However, several grains seem to be much smaller compared to the others, which may indicate cation segregation phenomena. 44 Nevertheless, the EDX-determined elemental maps indicate all cations constituting the PBSCF compound are distributed uniformly over the sample surface. The actual chemical composition was also found to be close to the stoichiometric one: the average atomic percentages for Pr, Ba, Sr, Co, and Fe were estimated to be 22.9 ± 3.5, 12.3 ± 2.3, 11.8 ± 0.7, 41.3 ± 5.4, and 11.7 ± 3.1 atom %, respectively, which coincides (within the error limit) with the nominal metal content in PBSCF.…”
Section: Phase Characterization and Microstructuralmentioning
confidence: 97%